Moose an agile reengineering environment. - Ducasse, Stéphane (Software engineering notes.)
Software systems are complex and difficult to analyze. Reengineering is a complex activity that usually involves combining different techniques and tools. MOOSE is an reengineering environment designed to provide the necessary infrastructure for building new tools and for integrating them. MOOSE centers on a language independent meta-model, and offers services like grouping, querying, navigation, and meta-descriptions. Several tools have been built on top of MOOSE dealing with different aspects of reengineering like: visualization, evolution analysis, semantic analysis, concept analysis or dynamic analysis.